Emergent litteracy and the transition from early years education to primary school - Cristina Manuela Sá (Escola Superior de Educação de Paula Frassinetti, 2015)
Developing emergent literacy is, undoubtedly, one of the most important issues in early-years education and at primary school namely in what concerns the transition between the two cycles. This is a context in which it is very important to explore the transversality of the mother tongue and its promotion through the teaching/learning process. This text aims to demonstrate that it is possible to implement such a program. In order to support our arguments, we present examples from short didactic interventions which took place mainly in contexts of professional training to become an early-years educator or a primary school teacher.